Identification of developmentally regulated expression of MuSK in astrocytes of the rodent retina. - Cheusova, Tatiana; Khan, Muhammad Amir; Enz, Ralf; Hashemolhosseini, Said (Journal of Neurochemistry, 2006)
One of the master regulators of postsynaptic neuromuscular synaptogenesis is the muscle-specific receptor tyrosine kinase (MuSK). In mammals prominent MuSK expression is believed to be restricted to skeletal muscle. Upon activation by nerve-derived agrin MuSK-dependent signalling participates in both the induction of genes encoding postsynaptic components and aggregation of nicotinic acetylcholine receptors (AChR) in the subsynaptic muscle membrane. Strikingly, expression of certain isoforms of nerve-derived agrin can also be detected in the CNS. In this study, we examined the expression of MuSK in the brain and eye of rodents. In the retina MuSK was expressed in astrocytes between postnatal days 7 and 14, i.e. at the time when the eyes open. We found that agrin was localized adjacent to MuSK-expressing astrocytes which in turn were detected close to the inner limiting membrane of the rodent retina. In summary, the presence of MuSK on retinal astrocytes suggests a novel role of MuSK signalling pathways in the CNS. © 2006 The Authors.
UnivIS-Import:2015-04-14:Pub.2006.med.IB.LPCIPDBI.identi
Keywords: Agrin; Astrocytes; Eye; Muscle-specific receptor tyrosine kinase; Neuromuscular junction; Retina